KEPERCAYAAN DAN PERSEPSI RISIKO TERHADAP KEPUTUSAN PEMBELIAN ONLINE - AYU RESA, NOVIA; LESTARI ANDJARWATI, ANIK (Jurnal Ilmu Manajemen (JIM), 2019)
This research aimed to analyze and discuss the influence of Trust and Perceived Risk on Online Purchase Decision on Lazada users. This is a causal research method with quantitative approach. The sampling method used judgmental with 210 respondents of Lazada users. The statistical analysis technique used is multiple linear regression with SPSS 23 program. The result shows that there is a significant effect of trust in online purchase decision and perceived risk of online purchase decision. The results also reveal that trust has a greater influence on online purchase decision compared to perceived risk. Keywords: online purchase decision; perceived risk; trust.